Philippines Monthly Economic Developments : August 2022 - World Bank (Washington, DC, 2022)
The Philippine economy expanded by 7.4 percent in the second quarter of 2022, anchored on robust domestic activity. The strong domestic environment stood in contrast with the weak external conditions which led to the modest growth in manufacturing and exports. In July, headline inflation further accelerated due to rising food and energy prices, and second-round effects from high fuel cost. To address inflation, the authorities have raised its key policy rates, rolled out fuel subsidy to vulnerable groups including public utility jeepney drivers and operators, farmers and fisherfolks, and provided cash transfers to poor households.